Continuous ozonation of urban wastewater: removal of antibiotics, antibiotic-resistant Escherichia coli and antibiotic resistance genes and phytotoxicity - Iakovides, I. C. (2019)
This work evaluated the removal of a mixture of eight antibiotics (i.e. ampicillin (AMP), azithromycin (AZM), erythromycin (ERY), clarithromycin (CIA), ofloxacin (OFL), sulfamethoxazole (SMX), trimethoprim (TMP) and tetracycline (TC)) from urban wastewater, by ozonation operated in continuous mode at different hydraulic retention times (HRTs) (i.e. 10, 20, 40 and 60 min) and specific ozone doses (i.e. 0.125, 0.25, 0.50 and 0.75 gO(3) gDOC(-1)). As expected, the efficiency of ozonation was highly ozone dose-and contact time-dependent. The removal of the parent compounds of the selected antibiotics to levels below their detection limits was achieved with HRT of 40 min and specific ozone dose of 0.125 gO(3) gDOC(-1). The effect of ozonation was also investigated at a microbiological and genomic level, by studying the efficiency of the process with respect to the inactivation of Escherichia coli and antibiotic-resistant E. coli, as well as to the reduction of the abundance of selected antibiotic resistance genes (ARG5). The inactivation of total cultivable E. coli was achieved under the experimental conditions of HRT 40 min and 0.25 gO(3) gDOC(-1), at which all antibiotic compounds were already degraded. The regrowth examinations revealed that higher ozone concentrations were required for the permanent inactivation of E. coli below the Limit of Quantification (<LOQ = 0.01 CFU mL(-1)). Also, the abundance of the examined ARGs (intl1, addA1, dfrA1, qacE Delta 1 and sal1) was found to decrease with increasing HRT and ozone dose. Despite the fact that the mildest operating parameters were able to eliminate the parent compounds of the tested antibiotics in wastewater effluents, it was clearly demonstrated in this study that higher ozone doses were required in order to confer permanent damage and/or death and prevent potential post-treatment re-growth of both total bacteria and ARB, and to reduce the abundance of ARGs below the LOQ, Interestingly, the mineralization of wastewater, in terms of Dissolved Organic Carbon (DOC) removal, was found to be significantly low even when the higher ozone doses were applied, leading to an increased phytotoxicity towards various plant species. The findings of this study clearly underline the importance of properly optimising the ozonation process (e.g. specific ozone dose and contact time) taking into consideration both the bacterial species and associated ARGs, as well as the wastewater physicochemical properties (e.g. DOC), in order to mitigate the spread of ARB&ARGs, as well as to reduce the potential phytotoxicity.